Tracing the patterns: fields, villages, and burial places in Lebanon. (2nd September 2021) - Flohr, Pascal; Bradbury, Jennie; ten Harkel, Letty
Abstract : Archaeological research in Lebanon often focuses on settlement from the Bronze Age to Roman periods, while surrounding landscapes, earlier and later periods are under-represented. Large datasets collecting information from all periods and site types, such as the Endangered Archaeology in the Middle East and North Africa (EAMENA) database, address this imbalance. EAMENA predominantly uses satellite imagery to identify archaeological sites and the threats posed to them, leading to the recognition of many previously unpublished sites, including abandoned buildings and agricultural terraces. Here we explore how such data can be used to trace patterns of settlement and landscape use. Transects running from coast to uplands in northern and southern Lebanon are compared: the results show profound differences between north and south, and between coastal and inland zones. The importance of large, holistic datasets for previously understudied site types and periods in piecing together past patterns of land use, subsistence economies, burial traditions and change over time are demonstrated.